(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
For many years one of the most common psychological complications in the IBS clinic is the occurrence of cognitive disorders, the etiology and risk factors of which from a psychological point of view remain insufficiently studied. In this connection, a deep comparative study of the main clinical, psychosocial and emotional-personal characteristics of elderly IBS patients with different dynamics (improvement and deterioration) of cognitive functioning after coronary bypass surgery was conducted. The study showed that patients with the worst cognitive development differed in a number of clinical and psychosocial characteristics (lifestyle characteristics); the presence of some degree of obesity in the history; the large number of affected arteries; Burdened with hereditary GCC male line.